An improved luciferase immunosorbent assay for ultrasensitive detection of antibodies against African swine fever virus - Wang, Qiongjie; Tian, Zhancheng; Yang, Jifei; Gao, Shandian; Du, Junzheng; Zhang, Hongge; Zhang, Zhonghui; Guan, Guiquan; Niu, Qingli; Yin, Hong (Frontiers in Microbiology, 2022)
African swine fever (ASF), caused by African swine fever virus (ASFV), is a fatal infectious disease of pigs and causes great socioeconomic losses globally. The reliable diagnostic method is critical for prevention and control of the disease. In this study, an improved Luciferase immunosorbent assay (LISA) for detecting ASF was developed using the cell lysates containing ASFV p35 protein fused with a reporter Nano-luciferase (p35-Luc protein). The improved method avoids the complicate procedures of immobilizing the serum samples with protein G in the normal LISA method, and replaced by directly coating the serum samples with carbonate buffer, therefore reduces the productive cost and simplifies the operation procedures. The p35-Luc LISA exhibited high specificity for anti-ASFV sera while no cross-reactions with the sera against other swine viruses. The detection limit of the p35-Luc LISA was shown to be at least four times higher than that of the p35 based indirect ELISA established in our lab. The receiver operating characteristic (ROC) analysis showed the 96.36% relative specificity and 96.97% relative sensitivity of the p35-Luc LISA with the cutoff values of 3.55 as compared to the commercial Ingezim p72-ELISA kit. Furthermore, a total of 248 serum samples were tested by both the p35-Luc LISA and commercial Ingezim p72-ELISA kit, and there was a high degree of agreement (97.6%, kappa=0.9753) in the performance of the two assays. Collectively, the improved LISA based on the p35-Luc protein could be used as a rapid, ultrasensitive, cost-effective and reliable diagnostic tool for serological survey of ASF in pig farms.